2004
DOI: 10.1111/j.1365-4632.2004.02048.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, noncomparative open study from Kuwait of the role of intravenous immunoglobulin in the treatment of toxic epidermal necrolysis

Abstract: Our experience of treating 12 patients with TEN using IVIG, in Kuwait, confirms that it is a safe and effective treatment for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 33 publications
1
25
1
3
Order By: Relevance
“…Numerous studies describe favorable outcomes following the use of IVIg. [63][64][65][66][67][68][69] Brown et al 70 and Bachot et al, 71 in contrast, reported poorer outcomes following treatment with IVIg. Several limitations of these two studies have been put forward.…”
Section: Intravenous Immunoglobulin (Ivig)mentioning
confidence: 93%
“…Numerous studies describe favorable outcomes following the use of IVIg. [63][64][65][66][67][68][69] Brown et al 70 and Bachot et al, 71 in contrast, reported poorer outcomes following treatment with IVIg. Several limitations of these two studies have been put forward.…”
Section: Intravenous Immunoglobulin (Ivig)mentioning
confidence: 93%
“…197 One-hundred percent survival was observed in a prospective study of 12 TEN patients from Kuwait treated with IVIG. 198 In a report of nine TEN patients treated with IVIG and pulse methylprednisolone, eight survived. Although the methylprednisolone is a confounding factor, it was nonetheless concluded that IVIG is a ''safe and valid'' therapy for TEN.…”
Section: Tnf-a Inhibitorsmentioning
confidence: 98%
“…Our experience of using IVIG in the treatment of TEN with a favourable outcome could be useful to those in other Arabian Gulf countries, whose citizens' genetic and environmental circumstances are similar to those of our patient. 15 …”
Section: Discussionmentioning
confidence: 99%